The Effect of Profitability and Firm Size on Firm Value Moderated by PROPER - Nur Islami, Rahmi; Sanjaya, M Feldi (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to determine the effect of profitability and company size on company value with environmental performance (PROPER) as a moderating variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The research questions asked are whether profitability and company size affect company value, and whether environmental performance (PROPER) can moderate this relationship. The research method used is a quantitative approach with moderated regression analysis (MRA) techniques, and secondary data was obtained from company annual reports and PROPER publications from the Ministry of Environment and Forestry (KLHK). The results show that profitability does not significantly affect company value, company size has a significant negative effect on company value, and environmental performance (PROPER) does not moderate the effect of profitability or company size on company value. These findings indicate that financial aspects are still the dominant factor in determining company value, while environmental performance is not yet fully considered by investors. The results of this study are expected to be taken into consideration by companies to improve transparency and environmental responsibility in order to strengthen company value in the eyes of investors.